Management of Learning Needs and Potential of Kindergarten Students - Hernawati,; Gaffar, M Fakry; Komariah, Aan; Yuniarsih, Tjutju; Wahab, Abdul Azis; Wahab, Abdul Azis (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of the study was to analyze the learning needs and learning potential of Kindergarten students so that the curriculum that was compiled was relevant to their characteristics. This study used a qualitative method in kindergarten in Bandung City with purposive sampling consisting of teachers, organizers, and parents. The results showed that the characteristics of kindergarten-age students, so that teachers can determine learning needs and potential. To meet learning needs in an effort to instill good character in students, character education is included in the curriculum. The effort by the Kindergarten to develop the potential of students through extra-curricular activities, such as dancing, drum bands, and pencak silat, was still not optimal. Not all teachers understood the curriculum developed at Kindergarten. Teachers' understanding of student characteristics and curriculum was very supportive of curriculum implementation in an effort to meet the learning needs of students and develop potential. Curriculum improvement should be performed by including all aspects that support the learning needs and learning potential of students as a whole so that learning inclusiveness is achieved.